Transformative Learning Model for Youth Life Skills Entrepreneurs in Poor Weavers Songket Palembang - Ayi Olim; Bertha N (Journal of Education and Learning (EduLearn), 2015)
Non-formal education serves to develop the potential of students with an emphasis on the mastery of knowledge and functional skills and professional attitude and personality development, is now understood as an alternative approach to the future education with an emphasis on the mastery of skills. transformative learning, life skills and entrepreneurship as a modality of model development. learner/ prospective participants learn from the lower-middle group (in the shadow of the transmission of learning) should be the owner of the learning process and should be able to identify the capabilities and environmental problems, reflect and take action in developing entrepreneurial abilities. The model requires changing patterns of transformative learning and utilization participants life skills learning, facilitation and management support from stakeholders